2022
DOI: 10.3389/fcimb.2022.862211
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA Sequencing Reveals Key Events When Different Giardia Life Cycle Stages Interact With Human Intestinal Epithelial Cells In Vitro

Abstract: Giardia intestinalis is a protozoan parasite causing diarrheal disease, giardiasis, after extracellular infection of humans and other mammals’ intestinal epithelial cells (IECs) of the upper small intestine. The parasite has two main life cycle stages: replicative trophozoites and transmissive cysts. Differentiating parasites (encysting cells) and trophozoites have recently been shown to be present in the same regions of the upper small intestine, whereas most mature cysts are found further down in the intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 77 publications
1
10
1
Order By: Relevance
“…intestinalis infection remains the subject of only a single recent study [ 32 ], which revealed IEC barrier breakdown linked to cyclic AMP/protein kinase A signalling during mature stages of the infection. Notably, the authors could by RNA sequencing (RNA-seq) not detect any IEC immune response during the early infection stage (first ~1.5 h), which stands in contrast to previous works in colorectal adenocarcinoma cell line cultures [ 20 , 22 ]. The reasons for these discrepancies are unclear.…”
Section: Introductioncontrasting
confidence: 68%
“…intestinalis infection remains the subject of only a single recent study [ 32 ], which revealed IEC barrier breakdown linked to cyclic AMP/protein kinase A signalling during mature stages of the infection. Notably, the authors could by RNA sequencing (RNA-seq) not detect any IEC immune response during the early infection stage (first ~1.5 h), which stands in contrast to previous works in colorectal adenocarcinoma cell line cultures [ 20 , 22 ]. The reasons for these discrepancies are unclear.…”
Section: Introductioncontrasting
confidence: 68%
“…The transcript of glcyclin 13874 increased in Giardia cells at the G1/S phase (1.5-fold). Interestingly, dual RNA sequencing analysis of Giardia interacting with human intestinal epithelial cells indicated that expression of 2 GlCDKs and 11 Glcyclins was decreased ( 45 ). The exact mechanisms of how the number of Glcyclins is varied and which Glcyclins exert their differential function in the Giardia cell cycle are important issues that need to be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of samples and their metadata can be found in Table S1, available in the online version of this article. The compiled data were published in six separate studies all using comparable library preparation protocols and Illumina sequencing chemistry [6,15,[18][19][20][21]. From this dataset and our described detection strategy, we identified a total of 42 candidate cis-splicing introns, including all eight introns previously characterized using laboratory methods, plus 34 novel ones.…”
Section: Bioinformatic Characterization Of Splicing Activity Identifi...mentioning
confidence: 99%
“…In this work, we gathered a collection of mRNA sequence data from six independent studies published between 2013 and 2022 [6,[16][17][18][19][20][21] and used these as the basis of a novel bioinformatics investigation of the gene models currently annotated in the G. duodenalis reference genome. Thus, our objectives in this study were to identify and characterize novel splicing activity to improve the gene models used for reference genome annotation.…”
Section: Introductionmentioning
confidence: 99%